Analysis of LAZISMU Bangkalan Financial Reports PSAK Perspective 109 - Muhammad Adnan; Luluk Hanifah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research aims to find out and analyze the presentation of LAZISMU Bangkalan's financial reports from the perspective of PSAK 109, namely regarding accounting for zakat and infaq/alms. PSAK 109 is an accounting standard that regulates financial reporting for entities managing zakat, infaq and alms. The analytical method used is a qualitative approach using a qualitative descriptive approach. The data used in this research comes from primary and secondary data from interviews with sources from LAZISMU Bangkalan and documentation of LAZISMU Bangkalan's financial reports. The results of the research show that in the financial reports LAZISMU Bangkalan has presented financial reports in accordance with the recording of PSAK 109. However, in its presentation in the financial reports LAZISMU Bangkalan has not fulfilled the five components, namely it is still not optimal in recording reports on changes in assets under management and notes on financial reports ( CALK).